Patriarchal attitudes in two selected isiXhosa literary texts. Issue 2 (3rd July 2019) - Made, Zoliswa
Abstract : This paper addresses problems concerning patriarchy and its undisputable connection to the demotion of women, using a feminist point of view. The question of patriarchal dominance and inequalities in African societies has been a trendy topic for decades and resulted from women's deprivation of the freedom of expression. This article seeks to show how the predominantly patriarchal isiXhosa culture is imbued with negative connotations towards women as depicted in two selected isiXhosa plays, namely Iinkunzi ezimbini by H Mothlabane and Inene nasi isibhozo by A Mtingane. The article also compares the presentation of the relationship between men and women in society, with particular emphasis on domestic and gender roles. The findings of this article, based on an analysis of the two literary texts, show to what extent isiXhosa culture is still inherently patriarchal. Finally, it is proposed that patriarchy is the reason for the problem of female subordination today.